2023
DOI: 10.3390/drones7110656
|View full text |Cite
|
Sign up to set email alerts
|

DELOFF: Decentralized Learning-Based Task Offloading for Multi-UAVs in U2X-Assisted Heterogeneous Networks

Anqi Zhu,
Huimin Lu,
Mingfang Ma
et al.

Abstract: With multi-sensors embedded, flexible unmanned aerial vehicles (UAVs) can collect sensory data and provide various services for all walks of life. However, limited computing capability and battery energy put a great burden on UAVs to handle emerging compute-intensive applications, necessitating them to resort to innovative computation offloading technique to guarantee quality of service. Existing research mainly focuses on solving the offloading problem under known global information, or applying centralized o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…This phenomenon of competing objectives is not confined to drone design. Studies by Anderson and Yang (2021) and Patel et al ( 2022) have demonstrated similar trade-offs in terrestrial robots, where the quest for speed can adversely affect stability and energy efficiency [28,29]. In the context of legged robots, the work of Tanaka and Lee (2022) further elucidated these trade-offs, specifically examining how modifications in leg linkage design impact overall robot performance [30].…”
Section: The Interplay Of Objectives In Robotic Designmentioning
confidence: 93%
“…This phenomenon of competing objectives is not confined to drone design. Studies by Anderson and Yang (2021) and Patel et al ( 2022) have demonstrated similar trade-offs in terrestrial robots, where the quest for speed can adversely affect stability and energy efficiency [28,29]. In the context of legged robots, the work of Tanaka and Lee (2022) further elucidated these trade-offs, specifically examining how modifications in leg linkage design impact overall robot performance [30].…”
Section: The Interplay Of Objectives In Robotic Designmentioning
confidence: 93%